Merangkul Perbedaan:Strategi Efektif untuk Mendorong Diversitas dan Inklusi dalam Pengembangan KaryawanIndustri Media Kreatif - Tumiar Berthalina Simatupang, S.I.Kom, M.I.Kom, Tumiar Berthalina Simatupang, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2024)
The creative media industry faces challenges in building a diverse and inclusive work environment. Lack of representation of diversity in creative and managerial teams, hidden biases, and lack of awareness are some of the obstacles. Implementation of plans to increase diversity and inclusion is hampered by cultural resistance, lack of management support, recruitment challenges, limited resources, and difficulties in measuring progress. Solutions require commitment from all levels of the company and a holistic approach to achieve significant change. Research methodsused include literature analysis and surveys to collect data from various sources as well as participatory observation to understand the work context in depth. The results of the discussion highlight the challenges of diversity and inclusion in the creative media industry, including bias, lack of representation, and their impact on innovation and content quality. Recommendations include inclusive policies, awareness training, promotion of equal opportunities, and building supportive work environments. Cooperation between industry, government, and society is needed to create sustainable change.